Facilitating different types of clusters - Mads Bruun Ingstrup (Management Revue, 2013)
This paper focuses on cluster facilitators and their efforts in facilitating the development of clusters. At present, the vast majority of literature presents a uniform image of cluster facilitators despite the fact that different types of clusters influence their role and purpose. Thus, the aim of this paper is to explore how the roles and purposes of cluster facilitators change when facilitating various cluster types, and the impact of those changes on the cluster facilitation performed. The findings show that cluster facilitators in Marshallian/Italian industrial district type of clusters play the role of match makers and organisers; in the Hub-and-spoke district type of clusters, the cluster facilitators perform the roles of developer and organiser; cluster facilitators in the Satellite industrial platform type of clusters are promoters and organisers; and in the State-anchored industrial district type of clusters, the cluster facilitators fulfil the roles of integrator and organiser. This conclusion is based on a multiple case study as well as on a selection of literature on clusters and cluster facilitation.
Keywords: O14; O20; R11; R58; 650; cluster facilitator; cluster; cluster type; case study; Regionales Cluster; Klassifikation